KONJUNGSI SUBORDINATIF DALAM NOVEL SLAUGHTER HOUSE FIVE KARYA KURT VONNEGUT, JR - Salawaney, Fonny Anita (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT This research entitled “Konjungsi Subordinatif dalam Novel Slaughter House Five Karya Kurt Vonnegut, Jr“ is written to fulfill the requirement of finishing S1 degree in English Department Faculty of Letter Sam Ratulangi University. The aims of the research to classify, to describe and to analyze subordinative conjunction in terms of its classification and meaning. In analyzing the data the writer uses descriptive method and by using the concept of Frank about classification and meaning. The results of this research show that the classification of subordinative conjunction that are used by Vonnegut, Jr. in the novel are subordinative conjunction single-word and subordinative conjunction two-word, meanings are subordinative conjunction can state time, contrast, cause, manner, condition, purpose, exception, and concessive. The meaning that used mostly by the author is subordinative conjunction states time. __________________ Keywords: Subordinative Conjunction, Slaughter House Five